Synthesis, Crystal Structure and Quantum Chemistry Calculation of Two Novel Compounds Derived from Amino-Phenol - Zhang, Pengfei; Fan, Yuhua; Bi, Caifeng; Zhang, Xia; Yan, Xingchen; Wu, Xiaojing (Asian Journal of Chemistry, 2014)
Two novel compounds [(Z)-3-(2-hydroxy-4-methylphenylimino)indolin-2-one][methanol] (A) and 4-[(Z)-(3-hydroxy-4-methoxyphenylimino)(phenyl)methyl]-3-methyl-1-phenyl-1H-pyrazol-5(4H)-one (B) derived from amino-phenol were synthesized and characterized by IR spectroscopy, elemental analysis and X-ray diffraction single-crystal analysis. Compound A crystallizes in monoclinic space group P21/c with a = 15.6637 (12) Å, b =12.3527 (9) Å, c = 7.4461 (6) Å, a = 90º, b = 100.9460 (10) º, g = 90º, V = 1414.53 (19) nm3, Z = 4, F (000) = 600, S = 1.055, R1 = 0392, wR2 = 0.0967. In addition, compound B crystallizes in triclinic, space group P-1 with a = 8.8111 (9) Å, b = 11.4716 (12) Å, c =11.4947 (14) Å, a = 115.376 (2) º, b = 99.5470 (10) º, g = 97.6320 (10) º, V = 1007.74 (19) nm3, Z = 2, F (000) = 420, S = 1.046, R1 = 0.0643, wR2 = 0.1479. Theoretical studies of compounds A and B were carried out by density functional theory B3LYP method. The results show that N (1), O (1) and O (2) of compound A and N (3), O (1) and O (2) of compound B are major active sites. Furthermore, N (1) in compound A is preferentially attacked by nucleophilic, followed by the N (3) in compound B. The theoretical studies show that compound A may have higher biological activity, such as anti-proliferative activity, compared with compound B. The result may be because that compound A is Schiff base and compound B occur proton transfer and tautomerism. CCDC: Compound A: 850318, Compound B: 938243.